Application of geographic information systems to the spatial distribution of illicit drug use: an analysis of the location of illicit drug seizures in a city - Chang, Ko-Lan; Tsai, Yu-Shu; Chan, Ta-Chien; Su, Lien-Wen; Chen, Chuan-Yu; Yen, Cheng-Fang; Yu, Pei-Jane; Hsu, Jui; Tsay, Wen-Ing; Chen, Wei J (Taiwan gong gong wei sheng za zhi (Taiwan gong gong wei sheng xue hui), 2016)
Objectives: To investigate the relationship between the use of Category Three or Four narcotics (illicit drugs) and geographical characteristics of the locations of seizures using the Geography Information System (GIS). Methods: Using the seizure data from a city over five years (2011-2015), we conducted a series of spatial analyses using ArcGIS software. We started with global analysis, and determined the seizure rate in different districts using visualized figures. Local analysis was then performed using two kinds of hot-spot analyses: Getis-Ord Gi* and kernel density analysis. Finally, the change rates in the number of seizures over the years for individual district were determined. Results: Estimates of the average number of nearest neighbors showed that the ratio Rs were all less than 1 for the five year period, indicating a strong spatial aggregation of the seizure of illicit drugs. The district-specific seizure rate showed that "high-rate areas" started with a few and then spread to others. Local analy